The Impact of Digital Communication on Online Purchasing Behavior among Indonesian Millennials: A Case Study of Tokopedia - Panigoro, Erwin; Harwani, Yuli; Permana, Dudi; Imaningsih, Erna Sofriana; Mahadewi, Erlina P. (UI Scholars Hub, 2023)
This article discusses the impact of digital communication on the online purchasing behavior of millennials in Indonesia, with a particular focus on transaction flow through the online commerce platform Tokopedia. The study aims to show that Tokopedia's digital communications determine users' attitudes and purchasing behavior. In this paper, the quantitative research method of causal design is adopted, and 210 respondents selected by simple random sampling are used as the sample size. The variables examined in this study include perceptions related to digital communication and online purchasing behavior, which are manipulated through different dimensions and indicators. The results show that perceived digital communication has a significant and positive impact on online purchasing behavior. Additionally, the study suggested that Tokopedia should develop a digital communication strategy to improve customer experience. Further research could expand the sample size and examine other variables for a more complete understanding of consumer behavior.